Villafàfila: explotación, mercaduría y usos de la sal. - Granja Alonso, Manuel de la (Estudios humanísticos. Geografía, historia y arte, 1993)
The first signs of Villafáfila of which we have documentary evidence, date back to the tenth century through the acquisition of some PAUSATAS from some small local landowners by the Monastery of Schagun. Exploitation of these salt mines was carried out until the eighteenth century. Most of the salts which were extracted were destined from human consumption and the remainder used in the production of gun powder. From the time of King Alfonso VII of Castille these salt mines were a royal monopoly and were traditionally leased for their exploitation and commercialization. This was controlled by the Law and culminated in 1338, with the Coronation of King Alfonso XI of Castille.